2021
DOI: 10.1039/d0nj04878j
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence quenching mechanism and the application of green carbon nanodots in the detection of heavy metal ions: a review

Abstract: This review article highlights the quenching mechanism and applications of green CNDs for the detection of metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 210 publications
0
57
0
Order By: Relevance
“…Both polymers were synthesized in high yields with P3 displaying a higher surface area, which can be explained either by the increased rigidity of the monomer core, therefore decreasing the flexibility of the polymer, or by the π–π stacking interactions between the pyrene-containing cores, which has been proven relevant in the synthesis of COFs, contributing to the increase in the rate of polymerization and the quality and surface area of the final materials . Notably, both materials P2 and P3 were extremely sensitive for Pd 2+ detection by fluorescence quenching, with P2 being able to sense down to 2 ppb or 0.019 μM (Figure d), making it considerably more sensitive than other solid materials like polymers or MOFs (400 and 44 ppb of Pd 2+ , respectively) and are even at the level of the best small molecule sensors reported . Moreover, the response was fast (within seconds), and both materials were extremely selective for Pd 2+ ; the fluorescence was not significantly affected by other cations such as Pt 2+ , Cu 2+ , Ni 2+ , Ag + , or Hg 2+ (Figure e, Figures S8–S13) and just slightly by Au 3+ 10 ppm of Au 3+ induces similar response as 0.1 ppm of Pd 2+ demonstrating the great potential of the materials as very sensitive and selective sensors for Pd 2+ traces in water.…”
Section: Resultsmentioning
confidence: 99%
“…Both polymers were synthesized in high yields with P3 displaying a higher surface area, which can be explained either by the increased rigidity of the monomer core, therefore decreasing the flexibility of the polymer, or by the π–π stacking interactions between the pyrene-containing cores, which has been proven relevant in the synthesis of COFs, contributing to the increase in the rate of polymerization and the quality and surface area of the final materials . Notably, both materials P2 and P3 were extremely sensitive for Pd 2+ detection by fluorescence quenching, with P2 being able to sense down to 2 ppb or 0.019 μM (Figure d), making it considerably more sensitive than other solid materials like polymers or MOFs (400 and 44 ppb of Pd 2+ , respectively) and are even at the level of the best small molecule sensors reported . Moreover, the response was fast (within seconds), and both materials were extremely selective for Pd 2+ ; the fluorescence was not significantly affected by other cations such as Pt 2+ , Cu 2+ , Ni 2+ , Ag + , or Hg 2+ (Figure e, Figures S8–S13) and just slightly by Au 3+ 10 ppm of Au 3+ induces similar response as 0.1 ppm of Pd 2+ demonstrating the great potential of the materials as very sensitive and selective sensors for Pd 2+ traces in water.…”
Section: Resultsmentioning
confidence: 99%
“…In general, two peaks in the range of 250-350 nm usually occur in the optical absorption spectrum for doped CDs. 83 Usually, these peaks are labelled as sp 2 C atoms and groups at the edge of CDs. The optical absorption spectrum for bare CDs near the UV region at 350 nm peak is yet unresolved.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…A strong emission band in the blue region (450 nm) contests the excitation absorption peak of n-p transition, whereas a weak emission band in the far UV region contests the p-p* excitation absorption peak. 83 Such a specific property observed by CDs is called an excitation-dependent emission that involves a bathochromic shift. Absorption in the visible region is low, which is responsible for the weak intensity.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, these methods have been based on organic dyes, which again suffer from limitations such as chemical instability and photoinstability and have narrow excitation and broad emission . Recently, inorganic nanoparticles such as quantum dots have replaced organic fluorophores to solve these challenges . The pH-sensitive carbon dots can also be efficiently used for biosensing. , These dots have improved properties such as biocompatibility, higher sensitivity, photostability, narrow emission wavelengths, and accuracy at a low cost. , There have been different applications of carbon quantum dots reported to date; Pang et al reported the application of pH-sensitive CQDs for urea and urease sensing in human blood serum in the ranges from 0.05 to 3.0 mM and 2.5 to 80 mg/L, respectively .…”
Section: Introductionmentioning
confidence: 99%